2012
DOI: 10.1007/s10616-011-9422-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxic perspective of Tamiflu

Abstract: The aim of this study was to investigate the genotoxic and/or cytotoxic effects of Tamiflu, commercial form of the oseltamivir antiviral and most frequently prescribed for the treatment of influenza infections, on cultured human peripheral lymphocytes by using sister chromatid exchange (SCE), chromosomal aberration (CA), and cytokinesis-blocked micronucleus (CBMN) assays. Cells were treated with 0.5, 1, 2 lg/mL oseltamivir, the Tamiflu capsule ingredient, for 24 or 48 h in the absence or presence of an exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The progesterone variant Megestrol acetate exhibited antagonisitic activity toward the AR with a submicromolar IC 50 value. From a biological standpoint, these observations make sense for the possible overall phenotypic consequences, as exemplified by the phenotypic feminization observed in animal models upon administration of Vinclozolin (Ila and Ilhan, 2012;Jamieson et al, 2009). From a compound screening perspective, these results suggested that the screening of multiple NHRs is likely to be necessary to gain a comprehensive understanding to the overall in vivo consequences.…”
Section: Steroid Compoundsmentioning
confidence: 95%
See 2 more Smart Citations
“…The progesterone variant Megestrol acetate exhibited antagonisitic activity toward the AR with a submicromolar IC 50 value. From a biological standpoint, these observations make sense for the possible overall phenotypic consequences, as exemplified by the phenotypic feminization observed in animal models upon administration of Vinclozolin (Ila and Ilhan, 2012;Jamieson et al, 2009). From a compound screening perspective, these results suggested that the screening of multiple NHRs is likely to be necessary to gain a comprehensive understanding to the overall in vivo consequences.…”
Section: Steroid Compoundsmentioning
confidence: 95%
“…Marketed under the trade name, Tamiflu, Oseltamivir is an antiviral drug used to treat influenza infection (Genentech USA, 2011). A study carried out by Ila and Ilhan (2012) using human lymphocytes showed that Oseltamivir decreased the proliferation index and nuclear division index, indicating it had a mild cytotoxic effect. However, the cytotoxic effects were no longer observed when adding an exogenous metabolic activation system (S9 mix) into the cell culture, suggesting that this particular cytotoxicity could be mitigated by metabolism (Ila and Ilhan, 2012).…”
Section: Nonsteroid Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Febrile seizures are a clinical diagnosis with still unknown exact etiology; however, even so, Choi et al [13] noted that high levels of proinflammatory cytokines released during viral infection may be linked to the onset of febrile seizures in pediatric patients, likely because of the still developing brain. Additionally, it is worth noting that oseltamivir has been shown to be weakly cytotoxic [14]; regardless of when our patient took oseltamivir, it was unlikely to have had any contribution to the onset of seizure-like activity.…”
Section: Our Suspicion For Rhinovirusmentioning
confidence: 79%
“…Our results support that situation. Same is true for oseltamivir which is not mutagenic at therapeutic and higher concentrations (Ila & Ilhan, 2012). Ribavirin has been tested widely for its mutagenicity through different models.…”
Section: Discussionmentioning
confidence: 99%